วิเคราะห์ชีวประวัติบรมกูรูแห่งโลกมลายู: ชัยคฺดาวูด อัลฟะฏอนีย์ - เจ๊ะโด ฮาเร๊ะ; การีนา อับดุลเลาะ (Al-HIKMAH Journal, 2018)
The study of the biography of SyeikhDaud al-Fathani is a descriptive study. The objective was to study the biography of Syeikh. The data recordis from his biography. Data were analyzed by criticism the inductive and deductive. The study was founded, Syeikh was born in Fatani, in 1183 AH. atKrueseh, Fatani.Syeikh was born in famous family of Patani’sulama. Preliminary studies by his family and the famous Fatani’sulamas. After he finish his studied from Fatani’sulamas, he went study with famous of ulamas of Acheh, Indonesia. After finish his studied, he went to Makkah to studies with famous Makkah’sulamas and went to studies with Madinah’sulama for several times.Syiekh has teach regular at al-Haram mosque, and also produced many of students and wrote many famous textbook and its still used as a textbook in Pondok of Fatani and in the nearly countries until now. Syiekh are recognized and appreciated by society as well and syiekh was actives in the academic field until the end. And was died at Mecca in 1262 AH.